A Miniaturized Meandered Dipole UHF RFID Tag Antenna for Flexible Application - Xiuwei Xuan; Lianrong Lv; Kun Li (International Journal of Antennas and Propagation)
A miniaturized meandered dipole antenna for UHF RFID tag is proposed. Different resonance frequencies and impedance can be achieved by adjusting the number of the meanders, which can help to reduce the size of the antenna. Due to the radiation patches, the input impedance of the antenna can be flexibly tuned in a large scale. The proposed antenna is printed on polyethylene (PET) substrate with a total volume of 48 mm × 13.7 mm × 0.5 mm. Modeling and simulation results show that the reflection coefficient of the antenna is less than −15 dB at 860–960 MHz. Experimental studies demonstrate that the minimum threshold power of the antenna is between 23 and 26 dBm and the measured read range is 3-4 m.